2019
DOI: 10.1507/endocrj.ej18-0407
|View full text |Cite
|
Sign up to set email alerts
|

Differences in the actions of adrenaline and noradrenaline with regard to glucose intolerance in patients with pheochromocytoma

Abstract: Glucose intolerance is often observed in patients with pheochromocytoma. However, it remains controversial issue that glucose intolerance on pheochromocytoma is caused by impaired insulin secretion and/or by increased insulin resistance. We aimed to reveal the mechanism of glucose intolerance on pheochromocytoma with regard to the type and amount of catecholamines released. We evaluated 12 individuals diagnosed with pheochromocytoma and who underwent surgery to remove it. We examined glycemic parameters before… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 20 publications
0
12
1
Order By: Relevance
“…Therefore, any associations with HOMAs should be interpreted cautiously, as in the case of the study reporting associations of U-NM with both insulin resistance and insulin secretion, although the association between U-NM and insulin resistance seemed to be primary. [17] However, in the present study, we did not observe such conflicting results. Fourthly, we evaluated insulin secretion using HOMA-β to represent insulin secretion in the fasting state, and did not measure any indices of glucose-stimulated insulin secretion.…”
Section: Discussioncontrasting
confidence: 80%
See 2 more Smart Citations
“…Therefore, any associations with HOMAs should be interpreted cautiously, as in the case of the study reporting associations of U-NM with both insulin resistance and insulin secretion, although the association between U-NM and insulin resistance seemed to be primary. [17] However, in the present study, we did not observe such conflicting results. Fourthly, we evaluated insulin secretion using HOMA-β to represent insulin secretion in the fasting state, and did not measure any indices of glucose-stimulated insulin secretion.…”
Section: Discussioncontrasting
confidence: 80%
“…[1,16] A previous study of patients with pheochromocytoma found that U-NM and U-M concentrations are differently associated with insulin resistance and insulin secretion: U-M is positively associated with impairment in insulin secretion, but not with insulin resistance, while U-NM is negatively associated with impairment of insulin secretion and positively associated with insulin resistance. [17] In the current study of people with CA concentrations within the physiologic range, the relationship between CAs and HOMA indices also differed according to the type of CA, with U-NM concentrations being significantly associated with insulin resistance, but no other association being identified. Taken together, these findings suggest that noradrenaline, but not adrenaline, excess causes insulin resistance at concentrations within the physiologic range, and when their concentrations reach the pathologic range, adrenaline has the most significant negative effect on insulin secretion.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“…A recent study elucidated the differences in the actions between epinephrine and norepinephrine on glucose intolerance in patients with phaeochromocytoma (40). The study investigated the association between the changes of urinary metanephrine/normetanephrine (metabolic product of epinephrine/norepinephrine) and those of HOMA-b/HOMA-IR from pre-operation to post-operation in 12 patients with phaeochromocytoma.…”
Section: The New Insight: Differences In the Actions On Glucose Intolmentioning
confidence: 99%
“…High tumor burden and increased hemodynamic volatility are associated with the greatest risk of fatal hypoglycemia [35-36]. Improved beta cell function and a comparison of pre-surgery to post-surgery status indicated a significant positive association to improved urinary metanephrines and a significant negative association to urinary normetanephrines [37]. Chen also reported that hypoglycemia may be more common in epinephrine-secreting tumors and after longer durations of operation [38].…”
Section: Reviewmentioning
confidence: 99%